Design And Implementation Of A Novel Top Edge Detection Algorithm-Based Smart Security System - A.S.M, Mukter-Uz-Zaman (2008)
In this research work, the author designed the peripheral interfacing modules such as ultrasonic sensor circuitry, moveable sensor plates by stepper motor circuitry, and image capture controlling circuit using Microcontroller (AVR ATmega8535), to develop the Smart Security System (SSS).